Dipolarity versus Polarizability and Acidity versus Basicity of Ionic Liquids as a Function of Their Molecular Structures. Issue 8 (21st January 2014) - Schade, Alexander; Behme, Nicole; Spange, Stefan
Abstract The four empirical solvent polarity parameters according to the Catalán scale—solvent acidity (SA), solvent basicity (SB), solvent polarizability (SP), and solvent dipolarity (SdP)—of 64 ionic liquids (ILs) were determined by the solvatochromic method. The SA parameter was determined solely by using [FeII(1, 10‐phenanthroline)2(CN)2] (Fe), the SB parameter by using the pair of structurally comparable dyes 3‐(4‐amino‐3‐methylphenyl)‐7‐phenylbenzo[1, 2‐b:4, 5‐b′]difuran‐2, 6‐dione (ABF) and 3‐(4‐N, N‐dimethylaminophenyl)‐7‐phenylbenzo[1, 2‐b:4, 5‐b′]‐difuran‐2, 6‐dione (DMe‐ABF), and the SP and SdP parameters by using the homomorphic pair of 4‐tert‐butyl‐2‐(dicyanomethylene)‐5‐[4‐(diethylamino)benzylidene]‐Δ3‐thiazoline (Th) and 2‐[4‐(N, N‐dimethylamino)benzylidene]malononitrile (BMN). The separation of SP and SdP for a set of 64 various ILs was performed for the first time. Correlation analyses of SP with physicochemical data related to ionization potentials of anions of ILs as well as with theoretical data show the correctness of the applied method. The found correlations of the Catalán parameters with each other and with the alkyl‐chain length of 1‐alkyl‐3‐methylimidazolium‐type ILs gives new information about interactions within ILs. An analytical comparison of the determined Catalán parameters with the established Kamlet–Taft parameters and the Gutmann acceptor and donor numbers is also presented.